Apple basic - Haskell, Richard E. 4 0 16; 5 (Englewood Cliffs, NJ : Prentice-Hall, 1982)
Provides an introduction to programming an Apple II computer in Applesoft BASIC.
A Spectrum book.;Includes index.;Reprint. Manila, Philippines : National Book Store, c1983.
Keywords: 2 -- 0; 6; Progamming. -- Apple II (Computer);BASIC (Computer program language).; 20; 2